On Lipschitz-like continuity of a class of set-valued mappings. (1st December 2020) - Bednarczuk, E. M.; Minchenko, L. I.; Rutkowski, K. E.
ABSTRACT: We study set-valued mappings defined by solution sets of parametric systems of equalities and inequalities. We prove Lipschitz-like continuity of these mappings under relaxed constant rank constraint qualification.